2018
DOI: 10.1038/s41598-018-33586-6
|View full text |Cite|
|
Sign up to set email alerts
|

The role of functional and structural interhemispheric auditory connectivity for language lateralization - A combined EEG and DTI study

Abstract: Interhemispheric connectivity between auditory areas is highly relevant for normal auditory perception and alterations are a major factor for the development of auditory verbal hallucinations. Surprisingly, there is no combined EEG-DTI study directly addressing the role of functional and structural connectivity in the same group of subjects. Accordingly, nothing is known about the relationship between functional connectivity such as gamma-band synchrony, structural integrity of the interhemispheric auditory pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 97 publications
0
19
1
Order By: Relevance
“…For example, it was shown that brain function is primarily shaped by anatomical modes computed from the spectral properties of the SC matrix (Abdelnour, Dayan, Devinsky, Thesen, & Raj, 2018 ; Atasoy, Donnelly, & Pearson, 2016 ; Huang et al, 2018 ; Preti & Van De Ville, 2019 ; Robinson, 2012 ). Finally, as most studies use functional magnetic resonance imaging (fMRI) data to evaluate FC because of its high spatial resolution, other functional modalities such as electro- or magneto-encephalography were also considered to explore the link between brain anatomy and function (Amico et al, 2017 ; Finger et al, 2016 ; Steinmann et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown that brain function is primarily shaped by anatomical modes computed from the spectral properties of the SC matrix (Abdelnour, Dayan, Devinsky, Thesen, & Raj, 2018 ; Atasoy, Donnelly, & Pearson, 2016 ; Huang et al, 2018 ; Preti & Van De Ville, 2019 ; Robinson, 2012 ). Finally, as most studies use functional magnetic resonance imaging (fMRI) data to evaluate FC because of its high spatial resolution, other functional modalities such as electro- or magneto-encephalography were also considered to explore the link between brain anatomy and function (Amico et al, 2017 ; Finger et al, 2016 ; Steinmann et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further exploring the data by also considering uncorrected p-values, revealed a cluster of segments in the splenium of the corpus callosum which showed an association with age of medium to large effect sizes (between 6 and 10% explained variance). The splenium is thought to connect sensory cortices or parietal brain regions (Schmahmann & Pandya, 2006), suggesting a relationship of the aging effect to the development of sensory or attentional integration between the hemispheres (e.g., Bozzali et al, 2012; Steinmann et al, 2018). Interestingly, here the aging trajectory resembled a saturation function: a rapid increase from childhood to adulthood is followed by a period of constant thickness that reaches into old age.…”
Section: Discussionmentioning
confidence: 99%
“…The corpus callosum as the major white-matter commissure, is a critical channel for the integration of information (e.g., Steinmann et al, 2018; Westerhausen, Gruner, Specht, & Hugdahl, 2009) and coordination of processing in the two cerebral hemisphere (e.g., Davis & Cabeza, 2015; Thiel et al, 2006). Thus, it appears little surprising that human neuroimaging studies report an association of individual differences in corpus callosum morphology with differences in higher cognitive abilities (e.g., Danielsen et al, 2020; Dunst, Benedek, Koschutnig, Jauk, & Neubauer, 2014; Hulshoff-Pol et al, 2006; Luders et al, 2007; Westerhausen et al, 2018).…”
mentioning
confidence: 99%
“…Resting-state EEG connectivity partly depends on the underlying white matter tract architecture 23,24,25,26 . With aging, even small changes in white matter integrity might lead to delayed and/or altered communications between brain regions, which could in turn alter cognitive functioning.…”
Section: Significance Statementmentioning
confidence: 99%